The Interpersonal Mindfulness in Parenting Scale in Mothers of Children and Infants: Factor Structure and Associations With Child Internalizing Problems - Burgdorf, Virginia; Szabó, Marianna (Frontiers in Psychology, 2021)
Objectives: Mindful parenting, measured by the Interpersonal Mindfulness in Parenting scale (IMP), is beneficial for parents and children. However, the IMP has not been validated in English-speaking parents. Further, little is known about whether mindful parenting is similar in parents of children vs. infants, or how it reduces child internalizing problems. We sought to validate the IMP in English-speaking mothers of children and infants, and to examine relationships between the facets of mindful parenting, child internalizing problems and parent variables related to internalizing. Methods: Using confirmatory factor analyses, we examined the fit of various models of mindful parenting in English-speaking community-recruited mothers of children aged 3–18 years (n = 396) and infants aged 0–2 years (n = 320). We used regression analyses to investigate relationships between the facets of mindful parenting, child internalizing problems, and parent variables including parental experiential avoidance, unhelpful beliefs about child anxiety and accommodation of child anxiety. Results: Mindful parenting can be measured in English-speaking mothers, using either a 5- or 6-factor, 29-item version of the IMP. These versions of the IMP operate similarly for mothers of children and infants. Child internalizing problems and related parent variables were best predicted by non-judgmental acceptance of parenting in mothers of children, and emotional self-awareness and non-reactivity in mothers of infants. Conclusions: The IMP is a valid measure of mindful parenting in English-speaking mothers of children and infants. Mindful parenting predicts child internalizing problems and related parent variables, suggesting that mindful parenting programs could benefit families of children with internalizing problems, potentially by reducing parental experiential avoidance, unhelpful beliefs about or accommodation of child anxiety.